2014
DOI: 10.5964/ejop.v10i2.703
|View full text |Cite
|
Sign up to set email alerts
|

“I Like My Body; Therefore, I Like Myself”: How Body Image Influences Self-Esteem—A Cross-Sectional Study on Italian Adolescents

Abstract: Puberty is a very important process for adolescents. Physiological changes and body modifications lead to great vulnerability. This vulnerability is connected to the adolescent’s perceptions of the uncertainty of outcomes due to the transformation of their infant body into an adult one. This cross-sectional study aims to better understand whether body image perception and satisfaction influence self-esteem in a sample of Italian male and female adolescents. A total of 242 adolescents (120 male and 122 female i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 45 publications
2
26
0
7
Order By: Relevance
“…This is in accordance with Gatti E in 2014, who mentioned that Girls appeared more dissatisfied with their bodies and seemed to be at more risk of engaging in dysfunctional eating behaviors than boys. [18] Also this is in agreement with Gillen MM et al who mentioned that male students were more satisfied with their body image than female students. [29] In addition, Yahia N et al stated that male students were less worried about their body image compared to females.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in accordance with Gatti E in 2014, who mentioned that Girls appeared more dissatisfied with their bodies and seemed to be at more risk of engaging in dysfunctional eating behaviors than boys. [18] Also this is in agreement with Gillen MM et al who mentioned that male students were more satisfied with their body image than female students. [29] In addition, Yahia N et al stated that male students were less worried about their body image compared to females.…”
Section: Discussionsupporting
confidence: 82%
“…[18,19] Body image is one of the most important psychological factors that affects adolescents' personality and behavior, because the adolescents view their body organs as separate parts, and each part plays a role in his/her personality. [20,21] The intense concern of body image would cause unfavorable outcomes such as poor health status, anxiety, depression, low self-esteem, and poor quality of life which eventually lead to body shape dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with Italian adolescents, Gatti and colleagues (2014) found significant relationships among weight, overall feelings towards one's appearance, the presence/absence of menarche, and self-esteem for girls. In contrast for boys, the only significant relationship was between height and self-esteem (Gatti et al 2014). Findings from this study underscore the importance of recognizing adolescence as an important time in the development of body image and that girls and boys differ in what may influence their body image.…”
Section: Body Image Self-esteem and Depression In Korean Adolescentsmentioning
confidence: 56%
“…Body fat changes linked to puberty (Gatti et al 2014;Siegel 2002) and rising rates of obesity in developed nations come in conflict for those living in societies that place a cultural emphasis on being thin. Perceptions of body image have a wide range of influences on an individual's life, and therefore research on body image is especially meaningful (Borges et al 2010).…”
Section: Body Image Self-esteem and Depression In Korean Adolescentsmentioning
confidence: 99%
“…Adolescence and youth is a period of life during which many important body changes take place that are determined by pubertal development. 2 Body image is one of the most important psychological factors that affects adolescents' personality and behaviour, because they view their body organs as separate parts, and each part plays a role in his/her personality. 3,4 Research has shown that the intense concern of body image can cause unfavourable outcomes such as poor health status, anxiety, depression, low self-esteem, and poor quality of life which eventually lead to body shape dissatisfaction.…”
mentioning
confidence: 99%